Axial Compression Behavior of Concrete-Encased CFST Columns - Abdulkhudhur, Raad; Elwi, Mohammed; Al-Quraishi, Hussein (Civil Engineering Journal, 2025)
Composite construction known as concrete-encased CFST is an outer covering of concrete surrounding a steel tube filled with concrete. It is employed as a structural member in multi-story buildings, large structures, bridges, and underground subway systems. Most of the literature deals with steel tubes filled with core concrete or concrete-encased steel tubes filled with core concrete with main reinforcement, but in the present study, CFST is used as conventional reinforcement. Therefore, five concrete-encased CFST columns and one normal reinforced concrete column were loaded axially. Variables were effects of CFST, percentage of steel tubes, outer concrete compressive strength, compressive strength of steel tube concrete, and ratio of unfilled steel tubes. The experimental test result of the reference concrete-encased CFST ultimate axial compression strength showed 65.1% strength of a conventional column. An increase in the ratio of CFST from 6.8% to 10.2% enhanced ultimate axial compression by 19.2% compared to the reference concrete-encased CFST column. Furthermore, a rise in the outer compression strength of the outer concrete from 15 MPa to 20 MPa resulted in an increase of 14.94% in ultimate axially compression loads. An increase of concrete compression strength within the steel tubes from 35 MPa to 45 MPa resulted in a slight increase of 0.62% in the ultimate load. The 16.8% reduction in the ultimate load, however, was due to the presence of a hollow steel tube inside the concrete-filled CFST. The validated finite element model was therefore employed to examine the effect of different parameters that affect the concrete column using a parametric study.